How 5 f Electron Polarisability Drives Covalency and Selectivity in Actinide N‐Donor Complexes. Issue 72 (2nd December 2021) - Köhler, Luisa; Patzschke, Michael; Schmidt, Moritz; Stumpf, Thorsten; März, Juliane
Abstract: We report a series of isostructural tetravalent actinide (Th, U−Pu) complexes with the N ‐donor ligand N, N' ‐ethylene‐bis((pyrrole‐2‐yl)methanimine) (H2 L, H2 pyren). Structural data from SC‐XRD analysis reveal [An(pyren)2 ] complexes with different An−Nimine versus An−Npyrrolide bond lengths. Quantum chemical calculations elucidated the bonding situation, including differences in the covalent character of the coordinative bonds. A comparison to the intensely studied analogous N, N′‐ ethylene‐bis(salicylideneimine) (H2 salen)‐based complexes [An(salen)2 ] displays, on average, almost equal electron sharing of pyren or salen with the An IV, pointing to a potential ligand‐cage‐driven complex stabilisation. This is shown in the fixed ligand arrangement of pyren and salen in the respective An IV complexes. The overall bond strength of the pure N ‐donor ligand pyren to An IV (An=Th, U, Np, Pu) is slightly weaker than to salen, with the exception of the Pa IV complex, which exhibits extraordinarily high electron sharing of pyren with Pa IV . Such an altered ligand preference within the early An IV series points to a specificity of the 5 f 1 configuration, which can be explained by polarisation effects of the 5 f electrons, allowing the strongest f electron backbonding from Pa IV (5 f 1 ) to the N donors of pyren. Abstract : A series of isostructural actinide (Th, U−Pu) complexes with N, N' ‐ethylene‐bis((pyrrole‐2‐yl)methanimine) (H2 L, H2 pyren) reveal different An−Nimine vs. An−Npyrrolide bond lengths and covalent character of the An−N bonds. Comparison to the [An(salen)2 ] complexes displays a slightly weaker overall bond strength of pyren to An IV (An=Th, U, Np, Pu), except for Pa IV .